PENGARUH PAJAK, MEKANISME BONUS, DAN TUNNELING INCENTIVE PADA INDIKASI MELAKUKAN TRANSFER PRICING - Saraswati, Rai Surya; Sujana, I Ketut (E-Jurnal Akuntansi; Vol 19 No 2 (2017), 2017)
This study was aimed to assess the effect of tax, bonus mechanism, and tunneling incentive on indication to performs transfer pricing. Secondary data was used by accessing the web www.idx.co.id . The manufacturing companies that are listed in Bursa Efek Indonesia year 2012-2015 was used as population. The sampling technique was purposive sampling. The sample size in amount of 100 observations. Data was collected in non-participant observation method and was analyzed using logistic regression.The results showed that both of tunneling incentive and tax was giving a positive effect on indication to performs transfer pricing while the bonus mechanism didn’t. The determination coefficients was 0.274, means 27.4% of indication to performs transfer pricing was affected by those variable, while the rest was explained by other variables. These results showed there are still many variables beyond this study to explain the transfer pricing.
Keywords: tax, bonus mechanism, tunneling incentive, transfer pricing